Analysis of hydrodynamic behavior in response to diverse pile arrangements adjacent to an impermeable dike - Sohail Iqbal; Norio Tanaka (Water Science)
Intense energy flow near the dike head significantly influences the development of the dike field zone (DFZ), momentum exchange zone (MEZ), and mainstream zone (MSZ), leading to potential partial or full failure of the dike in the MEZ. To address this, laboratory experiments were conducted to observe flow changes and rate of energy reduction around a single impermeable dike, with alterations made to the pile group length (HL: half-length = 11.5 cm and FL: full length = 23 cm), location (U: upstream, D: downstream), and shape (C: Circular, DV: Delta Van, ST: Streamlined tapered, APF: Angled Plate footing). Modifications in the MEZ flow structure were studied to mitigate concerns about intense energy vortices and dike head flows. These piles helped to assess factors like flow deflection, backwater rise, energy reduction rate, velocity fluctuations, and discharge distribution percentages across the zones. The data revealed that when the pile group length was increased from HL to FL, there was an inverse effect on depth-averaged velocity, MEZ discharge distribution percentage, and flow deflection toward the DFZ. Conversely, there was a direct influence on the rise in backwaters, rate of energy reduction, and discharge distribution percentages in the DFZ. The U-FL-APF pile dike showcased optimal results, displaying a reduction in maximum energy by 52% and streamwise velocity by 96%, while also increasing the backwater rise and discharge distribution by 22% and of only 5% in the MEZ, respectively, compared to a single impermeable dike. During flood events, these suggested measures can mitigate the intensified swirls formed in the DFZ, protect the dike head from direct momentum exchanges in the MEZ, and enhance flow deflection into the MSZ.